The Potential of Ultrasonic Membrane Anaerobic Systems in Treating Slaughterhouse Wastewater - Nour, A. H.; R. M., Yunus; Azhari, H. Nour; Abdulbari, Hayder A. (IWA Publishing, 2015)
Direct discharge of slaughterhouse wastewater causes serious environmental pollution due to its high chemical oxygen demand (COD), total suspended solids and biochemical oxygen demand. In this study, an ultrasonic-assisted membrane anaerobic system was used as a novel method for treating slaughterhouse wastewater. Six steady states were achieved, using concentrations of 7,800–13,620 mg/l for mixed liquor suspended solids and 5,359–11,424 mg/l for mixed liquor volatile suspended solids. Kinetic equations were used to describe the kinetics of treatment at organic loading rates of 3–11 kg COD/m3/d. The removal efficiency of COD was 94.8–96.5% with hydraulic retention times of 308.6–8.7 days. The growth yield coefficient was found to be 0.52 g VSS/g. COD was 0.21 d−1 and methane gas production rate was 0.24–0.56 l/g COD/d. Steady-state influent COD concentrations increased from 8,000 mg/l in the first steady state to 25,400 mg/l in the sixth steady state. The minimum solids retention time, θcmin obtained from the three kinetic models was 6–14.4 days. The k values were 0.35–0.519 g COD/g VSS.d and μmax values were between 0.26 and 0.379 d−1. The solids retention time decreased from 600 to 14.3 days. The complete treatment reduced the COD content and its removal efficiency reached to 94.8%.